Peningkatan Kompetensi Guru Melalui Pelatihan Pemanfaatan Media Pembelajaran Berbasis Augmented Reality - Ganinda, Nurhayati; Anjariyah, Deka; Imanah, Ulil Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The development of 21st century competencies such as critical thinking, creativity, collaboration, and communication has become a key focus in educational institution. These four competencies are closely linked to the use of technology in learning. Unfortunately, the rapid advancement of technology is often not matched by teachers' readiness, both in terms of knowledge and skills. To address this challenge, the team organized a workshop aimed at enhancing teachers' competencies in utilizing Augmented Reality-based learning media at SDN Kranggan 2. The target of this community service activity was all teachers at the school. The program was carried out in three stages: planning, implementation, and evaluation, using brainstorming, lecture, and question-and-answer methods. This workshop provided a platform for teachers to share experiences, receive material on technology use in education, and engage in interactive discussions. The results showed a very positive response from participants, with a satisfaction score of 97.4%. Participants were enthusiastic about the training on using Assemblr Studio, as it allowed them to create the needed learning media. Prior to this, they had never attended a training with similar content. In the feedback questionnaire, participants also suggested extending the duration of the workshop to allow for more material to be covered. Additionally, they expressed a desire for follow-up guidance so that all teachers could eventually create engaging learning media using Assemblr Studio and Canva.